1995
DOI: 10.1210/jcem.80.10.7559885
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic studies with intravenous and intranasal growth hormone-releasing peptide-2 in children of short stature.

Abstract: GH secretion is primarily regulated by the hypothalamic-releasing hormones GHRH and somatostatin. Additionally, several neurotransmitters act at the hypothalamus and pituitary to modulate GH release. The agents commonly used in clinical practice to diagnose GH deficiency, such as arginine, insulin and L-dopa, act through the neural GH network. Many children with a poor GH response to conventional agents have a significant serum GH response to iv GHRH. GH-releasing peptides (GHRPs) are synthetic peptides that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The synergistic release of GH induced when GHRP and GHRH are administered together intravenously is a consistent and sometimes dramatic finding in animals and in humans (14,19,28,29,102). This synergism cannot be reproduced in vitro.…”
Section: Synergismmentioning
confidence: 96%
See 1 more Smart Citation
“…The synergistic release of GH induced when GHRP and GHRH are administered together intravenously is a consistent and sometimes dramatic finding in animals and in humans (14,19,28,29,102). This synergism cannot be reproduced in vitro.…”
Section: Synergismmentioning
confidence: 96%
“…Glucose and free fatty acids only partially inhibit the GH response to hexarelin (87). Also, GHRPs have been used to diagnose GH deficiency in children (93,102,127 (94); GHRP-2, 0.3-3 Ilg/ kg subcutaneously once daily, 6 months]. In each study, height velocity was increased about 2.5-3.0 crn!…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…GHRP-2 has been shown to be effective in stimulating GH secretion in adults and children via the oral, intranasal as well as the iv route of administration [13]. It was well tolerated, able to stimulate GH secretion and enhanced growth velocity without side effects or toxicities in an eight months trial of prepubertal children with growth failure [14].…”
Section: Ghrp-2mentioning
confidence: 99%
“…Since GH-replacement therapy for GH-deficient patients has been successful in the clinical application of rhGH, several groups have examined the clinical efficacy of GHS in this disease. Pihoker's group administered peptidyl GHS, GHRP-2 or GHRH to 24 children of short stature [41] and found that 21 children responded to GHRP-2 and to GHRH, and showed enhanced GH release, although these children seemed to be a heterogeneous group of patients. The Merck group has investigated GH responses to orally administered MK-677 in GH-deficient adults who had been treated with rhGH during their childhood and did not have a pituitary or hypothalamic tumor, and had not undergone surgery or radiotherapy.…”
Section: Clinical Application Of Sm-130686mentioning
confidence: 99%